Thick electrode containing double-layer structure for all-solid-state battery and preparation method of thick electrode

By using a thick electrode with a double-layer structure in an all-solid-state lithium battery and using active materials of different sizes and structures to adjust the ion transmission speed, the problem of the electrode's transmission efficiency decreases and polarization in the rapid charging and discharge process is solved, and the electrochemical performance improvement and interface stability are enhanced.

CN119833568APending Publication Date: 2025-04-15SOUTH CHINA UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411994773.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the fast charging and discharging process, the thick electrode of all solid state lithium battery has problems such as decreasing ion and electron transmission efficiency, intensifying polarization and poor interface stability, resulting in degradation of battery performance and short cycle life.

Method used

A thick electrode with a double-layer structure is used to mix active materials of different sizes and structures in the electrodes to adjust the ion transfer speed, reduce polarization, and enhance the interface stability at high cutoff voltages.

Benefits of technology

It effectively improves the electrochemical performance of the electrode, reduces polarization phenomenon, enhances interface stability, thereby improving the energy density and cycle life of all solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833568A_ABST
    Figure CN119833568A_ABST
Patent Text Reader

Abstract

The invention discloses a thick electrode containing a double-layer structure for an all-solid-state lithium battery and a preparation method of the thick electrode. The thick electrode is composed of an upper layer and a lower layer, each layer contains different types of single or blended active materials, and the active materials are prepared according to a certain mass percent. The electrode directly adopts the polymer solid electrolyte as an adhesive, and the complementary advantages are realized by utilizing the characteristics of different active materials on the upper and lower layers. According to the design, the problem of high-voltage instability of an interface between the positive electrode in the battery and the electrolyte can be effectively relieved, and serious polarization caused by high load capacity is reduced, so that the high-surface-capacity all-solid-state lithium battery with long cycle life is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium batteries, and in particular relates to a thick electrode with a double-layer structure and a preparation method thereof. Background Art

[0002] Driven by energy transformation and technological advances in mobile devices, unprecedented requirements have been placed on the energy density and safety of battery systems. All-solid-state lithium batteries (ASSLBs) have shown significant advantages in safety and energy density because they use solid electrolytes (SSE) instead of traditional flammable liquid electrolytes. The introduction of solid electrolytes not only reduces the risk of thermal runaway of the battery, but also makes it possible to combine it with high-energy-density lithium metal anodes due to its high mechanical strength, thus breaking through the energy density upper limit of commercial lithium-ion batteries. Current research focuses on thin electrodes with low surface capacity. Although thin electrodes can provide good ion and electron transport properties, their energy density cannot meet the needs of high-capacity energy storage. Therefore, extending the technology to thick electrode applications has become the key to the research direction.

[0003] The use of thick electrodes in lithium-ion batteries has the potential to increase energy density, but it also faces many challenges. As the thickness of the electrode increases, the ion and electron transport paths within the electrode become longer, resulting in a decrease in transport efficiency. This problem is particularly evident during rapid charging and discharging. Specifically, the uneven lithium ion deintercalation reaction inside the electrode causes an unbalanced distribution of the electrochemical reaction in space. This uneven reaction further exacerbates the polarization inside the battery. Electrode polarization not only expands the distribution difference of the electrochemical potential, but also causes overcharge and discharge in some areas, destroying the crystal structure of the active material. In short, this uneven electrochemical reaction accelerates the degradation of battery performance, ultimately affecting the cycle life and safety of the battery.

[0004] In order to solve the above problems, researchers have proposed a variety of solutions. For example, by introducing vertically arranged microchannels in the electrode (Nano Energy, 2019, 61: 567-575) or linear inorganic lithium ion conductors (Adv. Mater. 2024, 36: 2312927) to accelerate Li + transmission, this method can effectively reduce Li +The tortuosity of transmission, reducing polarization and improving the electrochemical performance of thick electrodes. However, the above methods still face significant challenges in practical applications. Among them, the complex preparation process is the main limiting factor. Common preparation processes include freeze-drying pore formation, phase transition pore formation, and adjusting the arrangement direction of materials using magnetic methods. These processes are not only complex, but also require precise control of conditions and equipment, resulting in increased manufacturing costs and increased difficulty in large-scale production. In addition, liquid battery electrodes need to maintain a high porosity to ensure sufficient penetration of the electrolyte (CN115663108A; CN118412434A). In contrast, solid-state battery electrodes should minimize porosity while introducing solid electrolytes to ensure sufficient contact between the solid electrolyte and the active material and maintain the continuity of ion transmission. However, the introduction of vertically arranged microchannels may lead to an increase in ineffective voids, thereby reducing the electrochemical performance of the battery and affecting its overall volume energy density.

[0005] Compared with the modification strategies of thick electrodes of all-solid-state batteries, some efficient and simple modification strategies in liquid lithium batteries are worth learning from and thinking about. For example, researchers used the difference in reaction rates of active material particles of different sizes to design a double-layer thick electrode with a small particle size on the upper layer and a large particle size on the lower layer (Adv.Funct.Mater.2024,2410926) to regulate the ion transport rate inside the electrode, thereby reducing the concentration polarization inside the thick electrode. Other researchers solved the structural instability problem of electrode materials at high cut-off voltages by combining different active materials (Adv.Funct.Mater.2023,33,2304496), thereby improving the long cycle performance of the battery. In addition, the overall safety performance of the battery can be improved by coating a flame-retardant active material coating with an olivine structure on the electrode surface (Chem.Eng.J 2024,495,153344). Nevertheless, due to the differences between liquid and solid-state batteries, the modification strategy of liquid electrodes may not be applicable to solid-state batteries.

[0006] In summary, the field of solid-state lithium batteries still lacks a simple and feasible method for preparing thick electrodes, which can effectively improve the interfacial stability between active materials and electrolytes and reduce polarization, thereby further improving the overall energy density and electrochemical performance of solid-state batteries. Summary of the invention

[0007] In order to improve the various existing problems, the present invention proposes a thick electrode with a double-layer structure for an all-solid-state battery and a preparation method thereof. The thick electrode is divided into an upper and lower layer, and the mass proportion of the active material in each layer of the electrode remains unchanged. Only the type / composite ratio of the active material is changed to form a two-layer heterogeneous electrode. The present invention adjusts the ion transmission rate inside the electrode, reduces polarization and enhances the interface stability under high cut-off voltage by mixing active materials of different sizes and structures in the same coating or upper and lower coatings. At the same time, the present invention can also design blended active materials in a separate coating by utilizing the unique properties of different active materials to better adapt to the volume changes of active materials during the charging and discharging process and reduce contact losses. This research result provides a new idea for the design of thick electrodes for all-solid-state batteries and lays the foundation for the development of next-generation battery technology with higher energy density and safety.

[0008] The main purpose of the present invention is to provide a thick electrode with a double-layer structure for a solid-state battery.

[0009] The second purpose of the present invention is to provide a method for preparing a thick electrode with a double-layer structure for a solid-state battery.

[0010] The third object of the present invention is to provide an application of a thick electrode with a double-layer structure (including positive electrode materials such as lithium iron phosphate and lithium nickel cobalt manganese oxide) in a polyepoxy-based solid-state battery.

[0011] The present invention adopts a thick electrode with a double-layer structure, and improves the electrochemical kinetic reaction by matching different active materials, alleviates the more serious polarization effect in the thick electrode, enhances the interface stability, and improves the overall performance of the battery.

[0012] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0013] The present invention provides a method for preparing a thick electrode having a double-layer structure for a solid-state battery, which specifically comprises the following steps:

[0014] A high molecular polymer, a binder, a lithium salt and a solvent are mixed, heated and stirred to obtain a preliminary slurry. Then, the conductive agent and active materials of different types / different proportions are mixed, heated and stirred in corresponding proportions to obtain different electrode slurries. Subsequently, a preliminary thick electrode is obtained by scraping layer by layer.

[0015] The present invention makes full use of the characteristics of different active materials to achieve the construction of high-performance thick electrodes and improve the problems of severe polarization and high-voltage instability of the electrodes. Lithium iron phosphate has a nanometer-scale particle size and a stable olivine structure, exhibiting a low operating voltage, excellent thermal stability and a long cycle life. In contrast, lithium nickel cobalt manganese oxide has a micrometer-scale particle size and a less stable layered structure, and has low thermal stability, but its advantage is that it has a higher operating voltage and specific capacity. By organically combining these two active materials, the advantages of each can be retained while making up for each other's shortcomings. And combined with the combination of particles of different sizes, the electrochemical reaction kinetics of the electrode as a whole can be further accelerated, thereby effectively improving the electrochemical performance of the thick electrode. This method not only provides new ideas for electrode design, but also lays the foundation for the development of next-generation battery technology with high energy density, safety and reliability.

[0016] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0017] As a preferred technical solution of the present invention, the width of the first active layer is 30 to 100 mm, for example, 30, 40, 50, 60, 70, 80, 90 or 100 mm, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0018] Preferably, the thickness of the another electrode layer is almost the same as the thickness of the first layer.

[0019] As a preferred technical solution of the present invention, the conductive agent includes any one of acetylene black, carbon nanotubes, carbon fibers, carbon black or graphene, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of carbon nanotubes and acetylene black, a combination of carbon nanotubes and graphene, a combination of carbon fibers and graphene, a combination of carbon black and carbon nanotubes, and a combination of carbon nanotubes and carbon fibers and graphene.

[0020] Preferably, the conductive agent is a combination of carbon nanotubes and carbon black (mass ratio 1:2).

[0021] Each layer of active main material includes any one of lithium cobalt oxide, lithium iron manganese phosphate, lithium iron phosphate, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two of them. Typical but non-limiting examples of the combination include a combination of lithium cobalt oxide and lithium iron manganese phosphate, a combination of lithium iron manganese phosphate and lithium iron phosphate, and a combination of lithium iron phosphate and lithium nickel cobalt aluminum oxide.

[0022] Preferably, the active main material is lithium iron phosphate, lithium iron manganese phosphate, lithium nickel cobalt manganese oxide, a blend of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide, or a blend of lithium iron phosphate and lithium nickel cobalt manganese oxide.

[0023] As a preferred technical solution of the present invention, the polymer solid electrolyte is calculated by mass fraction as follows:

[0024] 40-50 parts of lithium salt;

[0025] 50-120 parts of high molecular polymer;

[0026] Preferably, in terms of mass fractions,

[0027] 44.39 parts of lithium salt;

[0028] 100 parts of high molecular polymer;

[0029] Furthermore, the high molecular polymer is one or a combination of at least two of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile;

[0030] Preferably, the high molecular polymer is a combination of polyethylene oxide and polyvinylidene fluoride (mass ratio 3:1);

[0031] Furthermore, the lithium salt is one or a combination of at least two of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, and lithium bis(oxalate borate);

[0032] Preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl imide);

[0033] Furthermore, the molar ratio of lithium salt to high molecular polymer in the solid electrolyte is 1:15-20;

[0034] Preferably, the molar ratio of lithium salt to high molecular polymer in the solid electrolyte is 1:15;

[0035] As a preferred technical solution of the present invention, the active layer is calculated by mass fraction:

[0036] Active substance 70 parts;

[0037] Solid electrolyte 25 parts;

[0038] Conductive agent 5 parts.

[0039] As a preferred technical solution of the present invention, the solid electrolyte in the thick electrode only includes a polymer solid electrolyte;

[0040] Preferably, the solid electrolyte in the thick electrode is a polymer solid electrolyte.

[0041] As a preferred technical solution of the present invention, the solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide and acetonitrile.

[0042] Preferably, the solvent is N,N-dimethylformamide.

[0043] As a preferred technical solution of the present invention, the temperature is 70-100°C, the pressure is 8-15MPa, and the time is 5-15min.

[0044] Preferably, the hot pressing temperature is 80°C, the hot pressing time is 10 min, and the hot pressing pressure is 10 MPa.

[0045] As a preferred technical solution of the present invention, the vacuum drying temperature is 60-100°C, and the vacuum drying time is 8-48h.

[0046] Preferably, the vacuum drying temperature is 80° C. and the vacuum drying time is 12 h.

[0047] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0048] (1) Highly adaptable double-layer structure: Through the upper and lower double-layer electrode structure, the combination of different active materials is used to effectively cope with the volume change during charging and discharging, reduce contact loss, and improve the stability of the electrode.

[0049] (2) High energy density and safety: Through the organic combination of olivine structure positive electrode materials and layered structure positive electrode materials, the solution retains the respective advantages of the two materials, ensuring high energy density while improving the safety and cycle life of the battery.

[0050] (3) By mixing active materials of different particle sizes, the ion transport rate of the electrode is improved, the electrochemical polarization phenomenon is reduced, and the interface stability under high-voltage conditions is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The double-layer thick electrode all-solid-state battery prepared in Example 1 has an upper layer with active material near the solid electrolyte side, and a lower layer with active material of lithium iron phosphate electrode at 0.1 mA cm -2 The first cycle charge and discharge curve.

[0052] Figure 2 The double-layer thick electrode all-solid-state battery prepared in Example 3, in which the upper and lower active materials are both lithium nickel cobalt manganese oxide, is -2 The first cycle charge and discharge curve.

[0053] Figure 3 The double-layer thick electrode all-solid-state battery prepared in Example 4, in which both the upper and lower active materials are lithium iron phosphate, is -2 The first cycle charge and discharge curve.

[0054] Figure 4Schematic diagram of the structure of a thick electrode with a double-layer structure for an all-solid-state battery in the present invention.

[0055] Figure 5 The double-layer thick electrode all-solid-state battery prepared in Example 1 has an upper layer with active material near the solid electrolyte side, and a lower layer with active material of lithium iron phosphate electrode at 0.1 mA cm -2 Cyclic charge and discharge curve diagram.

[0056] Figure 6 The double-layer thick electrode all-solid-state battery prepared in Example 3, in which the upper and lower active materials are both lithium nickel cobalt manganese oxide, is -2 Cyclic charge and discharge curve diagram.

[0057] Figure 7 The double-layer thick electrode all-solid-state battery prepared in Example 4, in which both the upper and lower active materials are lithium iron phosphate, is -2 Cyclic charge and discharge curve diagram. DETAILED DESCRIPTION

[0058] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0059] Example 1

[0060] This embodiment provides a double-layer thick electrode in which the active material on the upper layer close to the solid electrolyte side is a lithium iron phosphate electrode and the lower layer is a lithium nickel cobalt manganese oxide electrode. The preparation method of the double-layer thick electrode includes the following steps:

[0061] (1) 0.4439 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.2500 g of polyvinylidene fluoride (PVDF) were weighed and placed in a flat-bottom flask, and then 20.0000 g of N,N-dimethylformamide (DMF) was added. The mixture was stirred at 60° C. for 2 h to form a uniform suspension. Then, 0.7500 g of polyethylene oxide (PEO) was added and stirred at 60° C. for 8 h to obtain slurry 1.

[0062] (2) Add 0.5 g of lithium nickel cobalt manganese oxide, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes to slurry 1 and stir and disperse them, wherein the content of lithium nickel cobalt manganese oxide is 70 wt %, and the content of carbon black and carbon nanotubes (mass ratio is 2:1) is 5 wt %, to obtain a uniform slurry 2; add 0.5 g of lithium iron phosphate, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes to slurry 1 and stir and disperse them, wherein the content of lithium nickel cobalt manganese oxide is 70 wt %, and the content of carbon black and carbon nanotubes (mass ratio is 2:1) is 5 wt %, to obtain a uniform slurry 3, and mix them evenly.

[0063] (3) Slurry 2 is first coated on the current collector aluminum sheet to obtain the lower electrode. After the solvent evaporates to a suitable state, slurry 3 is coated on the previous electrode again, with each layer having a thickness of 50 μm.

[0064] (4) After the second layer evaporates to a suitable state, hot pressing is performed, with the hot pressing temperature set at 80°C, the pressure at 10 MPa, and the time at 10 min. After vacuum drying at 80°C for 12 h, the pellets are pressed into a 14 mm diameter disc for later use.

[0065] (5) The double-layer thick electrode prepared in Example 1, the PEO-based composite solid electrolyte and the lithium metal negative electrode are assembled into an all-solid-state double-layer electrode battery (its structure is as follows) Figure 4 shown).

[0066] The all-solid-state high-area capacity battery was subjected to an electrochemical performance test (the electrochemical performance test was conducted based on a Neware battery testing system, using a constant current charge / discharge method: for double-layer thick electrode solid-state batteries, the charge and discharge voltage window was set to 2.5-4.3V).

[0067] Figure 1 The double-layer thick electrode all-solid-state battery prepared in Example 1 has an upper layer with active material near the solid electrolyte side, and a lower layer with active material of lithium iron phosphate electrode at 0.1 mA cm -2 The first cycle charge and discharge curve of the battery. The discharge capacity in the first cycle reached 167.4 mAh / g, and it can be seen that the polarization of the battery is small and the coulombic efficiency is high. Figure 5 The double-layer thick electrode all-solid-state battery prepared in Example 1 has an upper layer with active material near the solid electrolyte side, and a lower layer with active material of lithium iron phosphate electrode at 0.1 mA cm -2 Cyclic charge and discharge curve diagram.

[0068] Example 2

[0069] This embodiment provides a double-layer thick electrode in which the active materials on the upper layer close to the solid electrolyte side are lithium iron phosphate and lithium nickel cobalt manganese oxide electrodes, and the lower layer is a lithium nickel cobalt manganese oxide electrode, comprising the following steps:

[0070] (1) 0.4439 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.2500 g of polyvinylidene fluoride (PVDF) were weighed and placed in a flat-bottom flask, and then 20.0000 g of N,N-dimethylformamide (DMF) was added. The mixture was stirred at 60° C. for 2 h to form a uniform suspension. Then, 0.7500 g of polyethylene oxide (PEO) was added and stirred at 60° C. for 8 h to obtain slurry 1.

[0071] (2) 0.5 g of lithium nickel cobalt manganese oxide, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes were added to slurry 1 and stirred and dispersed, wherein the content of lithium nickel cobalt manganese oxide was 70 wt %, and the content of carbon black and carbon nanotubes (mass ratio was 2:1) was 5 wt %, to obtain a uniform slurry 2. 0.25 g of lithium nickel cobalt manganese oxide, 0.25 g of lithium iron phosphate, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes were added to slurry 1 and stirred and dispersed, wherein the content of lithium nickel cobalt manganese oxide was 35 wt %, the content of lithium iron phosphate was 35 wt %, and the content of carbon black and carbon nanotubes (mass ratio was 2:1) was 5 wt %, to obtain a uniform slurry 3.

[0072] (3) Slurry 2 is first applied on the current collector aluminum sheet to obtain the electrode close to the battery shell. After the solvent evaporates to a suitable state, slurry 3 is applied on the previous electrode, with each layer thickness of 50 μm.

[0073] (4) After the second layer evaporates to a suitable state, hot pressing is performed, with the hot pressing temperature set at 80°C, the pressure at 10 MPa, and the time at 10 min. After vacuum drying at 80°C for 12 h, the pellets are pressed into a 14 mm diameter disc for later use.

[0074] (5) The double-layer thick electrode prepared in Example 2 is assembled with a PEO-based composite solid electrolyte and a lithium metal negative electrode into an all-solid-state double-layer electrode battery.

[0075] The all-solid-state high-area capacity battery was subjected to an electrochemical performance test (the electrochemical performance test was conducted based on a Neware battery testing system, using a constant current charge / discharge method: for double-layer thick electrode solid-state batteries, the charge and discharge voltage window was set to 2.5-4.3V).

[0076] Example 3

[0077] This embodiment provides a double-layer thick electrode in which the active materials are all lithium nickel cobalt manganese oxide, and the preparation method of the double-layer thick electrode comprises the following steps:

[0078] (1) 0.4439 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.2500 g of polyvinylidene fluoride (PVDF) were weighed and placed in a flat-bottom flask, and then 20.0000 g of N,N-dimethylformamide (DMF) was added. The mixture was stirred at 60° C. for 2 h to form a uniform suspension. Then, 0.7500 g of polyethylene oxide (PEO) was added and stirred at 60° C. for 8 h to obtain slurry 1.

[0079] (2) 0.5 g of lithium nickel cobalt manganese oxide, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes were added to slurry 1 and stirred and dispersed, wherein the content of lithium nickel cobalt manganese oxide was 70 wt %, and the content of carbon black and carbon nanotubes (mass ratio was 2:1) was 5 wt %, to obtain a uniform slurry 2.

[0080] (3) Slurry 2 is first applied on the current collector aluminum sheet to obtain an electrode close to the battery shell. After the solvent evaporates to a suitable state, slurry 2 is applied again on the previous electrode, with each layer having a thickness of 50 μm.

[0081] (4) After the second layer evaporates to a suitable state, hot pressing is performed, with the hot pressing temperature set at 80°C, the pressure at 10 MPa, and the time at 10 min. After vacuum drying at 80°C for 12 h, the pellets are pressed into a 14 mm diameter disc for later use.

[0082] (5) The double-layer thick electrode prepared in Example 2 is assembled with a PEO-based composite solid electrolyte and a lithium metal negative electrode into an all-solid-state double-layer electrode battery.

[0083] The all-solid-state high-area capacity battery was subjected to an electrochemical performance test (the electrochemical performance test was conducted based on a Neware battery testing system, using a constant current charge / discharge method: for double-layer thick electrode solid-state batteries, the charge and discharge voltage window was set to 2.5-4.3V).

[0084] Figure 2 The double-layer thick electrode all-solid-state battery prepared in Example 3, in which the upper and lower active materials are both lithium nickel cobalt manganese oxide, is -2 The first cycle charge and discharge curve. Figure 6 The double-layer thick electrode all-solid-state battery prepared in Example 3, in which the upper and lower active materials are both lithium nickel cobalt manganese oxide, is -2 Cyclic charge and discharge curve diagram.

[0085] Example 4

[0086] This embodiment provides a double-layer thick electrode in which both upper and lower layers of active materials are lithium iron phosphate. The preparation method of the double-layer thick electrode comprises the following steps:

[0087] (1) 0.4439 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.2500 g of polyvinylidene fluoride (PVDF) were weighed and placed in a flat-bottom flask, and then 20.0000 g of N,N-dimethylformamide (DMF) was added. The mixture was stirred at 60° C. for 2 h to form a uniform suspension. Then, 0.7500 g of polyethylene oxide (PEO) was added and stirred at 60° C. for 8 h to obtain slurry 1.

[0088] (2) 0.5 g of lithium iron phosphate, 0.0238 g of carbon black, and 0.0119 g of carbon nanotubes were added to slurry 1 and stirred and dispersed, wherein the content of lithium nickel cobalt manganese oxide was 70 wt %, and the content of carbon black and carbon nanotubes (mass ratio was 2:1) was 5 wt %, to obtain a uniform slurry 2.

[0089] (3) Slurry 2 is first applied on the current collector aluminum sheet to obtain an electrode close to the battery shell. After the solvent evaporates to a suitable state, slurry 2 is applied again on the previous electrode, with each layer having a thickness of 50 μm.

[0090] (4) After the second layer evaporates to a suitable state, hot pressing is performed, with the hot pressing temperature set at 80°C, the pressure at 10 MPa, and the time at 10 min. After vacuum drying at 80°C for 12 h, the pellets are pressed into a 14 mm diameter disc for later use.

[0091] (5) The double-layer thick electrode prepared in Example 2 is assembled with a PEO-based composite solid electrolyte and a lithium metal negative electrode into an all-solid-state double-layer electrode battery.

[0092] The all-solid-state high-area capacity battery was subjected to an electrochemical performance test (the electrochemical performance test was conducted based on a Neware battery testing system, using a constant current charge / discharge method: for double-layer thick electrode solid-state batteries, the charge and discharge voltage window was set to 2.5-4.0V).

[0093] Figure 3 The double-layer thick electrode all-solid-state battery prepared in Example 4, in which both the upper and lower active materials are lithium iron phosphate, is -2 The first cycle charge and discharge curve. Figure 7 The double-layer thick electrode all-solid-state battery prepared in Example 4, in which both the upper and lower active materials are lithium iron phosphate, is -2 Cyclic charge and discharge curve diagram.

[0094] Example 5

[0095] This embodiment provides a double-layer thick electrode in which the active material on the upper layer close to the solid electrolyte side is a lithium iron phosphate electrode and the lower layer is a lithium nickel cobalt manganese oxide electrode, including the following steps: 1w% pentafluorophenylacetic acid is added to slurry 2 as an electrolyte additive, and the remaining steps are the same as implementation case 2.

[0096] The all-solid-state high-area capacity battery was subjected to an electrochemical performance test (the electrochemical performance test was conducted based on a Neware battery testing system, using a constant current charge / discharge method: for double-layer thick electrode solid-state batteries, the charge and discharge voltage window was set to 2.5-4.0V).

[0097] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A thick electrode with a double-layer structure for an all-solid-state lithium battery, characterized in that: The coatings containing a single or mixed active material are used as the upper and lower layers of the electrode respectively; each electrode layer includes an active material, a conductive agent and a polymer solid electrolyte; the mass percentage of the active material in the upper and lower layers is the same.

2. The thick electrode with double-layer structure for all-solid-state lithium battery according to claim 1, characterized in that: The thickness of the upper and lower coatings of the prepared electrode is almost the same, ranging from 30 to 100 μm.

3. The thick electrode with double-layer structure for all-solid-state lithium battery according to claim 1, characterized in that: The active material used in each layer of the thick electrode includes a lithium-ion battery positive electrode material; The positive electrode material of the lithium-ion battery includes one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide or lithium-rich manganese-based lithium positive electrode materials; The conductive agent includes at least one of acetylene black, superconducting carbon black BP2000, carbon nanotubes, carbon fibers or graphene.

4. The thick electrode with double-layer structure for all-solid-state lithium battery according to claim 1, characterized in that: The electrode directly uses a polymer solid electrolyte as a binder.

5. The thick electrode with double-layer structure for all-solid-state lithium battery according to claim 1, characterized in that: The polymer solid electrolyte used as a binder in the thick electrode includes the following substances in parts by mass: Lithium-ion battery additives 3-10 parts; 40-50 parts of lithium salt 60-120 parts of high molecular weight polymer The high molecular polymer is one or more of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile; The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, and lithium bis(oxalate borate); The lithium-ion battery additive is one or more of lithium difluorophosphate, lithium difluorooxalatoborate, and lithium difluorobisoxalatephosphate; The molar ratio of lithium salt to high molecular polymer in the solid electrolyte is 1:15 to 1:

20.

6. A method for preparing a thick electrode with a double-layer structure for an all-solid-state lithium battery according to any one of claims 1 to 5, characterized in that: The steps include: The polymer solid electrolyte and the solvent are mixed and stirred to obtain a preliminary slurry, and then the active material and the conductive agent are mixed into the preliminary slurry in different proportions, and stirred evenly to obtain different electrode slurries. Subsequently, a thick electrode is prepared by multi-layer scraping, and finally a thick electrode with a double-layer structure is obtained by hot pressing and vacuum drying.

7. The preparation method according to claim 6, characterized in that: The active layer of the thick electrode comprises the following substances in terms of mass fractions: 15-30 parts of solid electrolyte; Conductive agent 5-10 parts; Active material 40-80 parts.

8. The method for preparing a thick electrode with a double-layer structure according to claim 6, characterized in that: The solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylformamide and acetonitrile.

9. The method for preparing a thick electrode with a double-layer structure according to claim 6, characterized in that: The temperature of the hot pressing step is 70-100° C., the pressure is 8-15 MPa, and the time is 5-15 min; the temperature of the vacuum drying is 60-100° C., and the time of the vacuum drying is 8-48 h.

10. Application of the thick electrode with double-layer structure as claimed in any one of claims 1 to 5 in an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Preparation method of high-porosity battery pole piece and solid-state battery

    CN115663108A

  • Positive pole piece, preparation method thereof and secondary battery

    CN118412434A

  • Preparation method of electrode of all-solid-state lithium ion battery

    CN111710827A

  • Positive plate for solid-state battery, and preparation method and application thereof

    CN112786840A

  • Battery pole piece of all-solid-state battery as well as preparation method and application of battery pole piece

    CN115513407A